PERCEPTION AND RECOGNITION OF CONCEPTS OF SPEECH ACTS IN VOCAL COMMUNICATION - E. I. Grigoriev (Vestnik MGIMO-Universiteta)
Questions of conceptualization of notions are main in recognizing the meanings emerging in the communication process. All levels of the linguistic system are involved in the conceptualization of the surrounding world. In people's minds there are concepts represented lexically, morphologically and syntactically. The role of prosody in the formation of concepts is not investigated yet. The aim of the paper is to validate the process of conceptualization of illocutionary acts on the basis of the perception of the prosodic structure of spoken utterances in a speech interaction. In modern linguistics there are different approaches to the definition of the concept. This article briefly reviews some definitions specific for native linguistics. The notion of the concept being the basis of the present research is a mental image of reality around us, which is stored in the human mind and arises at verbal or visual perception of the linguistic sign. Speech act should be seen as a concept of the speech actions / behavior in a particular situation. It forms both at the level of vocabulary, and at the participation of the prosodic components of speech. Especially the role of prosody increases in the case of one-way communication in the illocutivs with the same lexical composition but different prosodic structures. The factors that determine the formation of concepts of speech acts, are the level stratifications of tone and volume, temporary compression or extension of different zones of expression, rhythm and character of syllabic stress. These phenomena are due to national features and may influence the flow of cross-cultural communication.